The Influence of Perceived Value and Brand Image on Customer Citizenship Behavior is Mediated by Customer Loyalty - Dodi Ria Atmaja; Muniroh (Majalah Ilmiah Bijak, 2025)
The dynamics of contemporary business competition require companies to understand consumer behavior, which is not only limited to purchasing activities, but also extends to active participation in supporting brands through customer citizenship behavior. Previous research has shown that perceived value and brand image play important antecedents in shaping customer loyalty, but the mechanism by which these two variables influence customer citizenship behavior through loyalty mediation still requires further investigation. This study aims to analyze the influence of perceived value and brand image on customer citizenship behavior with customer loyalty as a mediating variable. The research method used a quantitative design with an explanatory research approach and a purposive sampling technique on 35 respondents who met the research criteria. Data were collected through a structured questionnaire using a 5-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results showed that perceived value had a positive and significant effect on customer citizenship behavior (β = 0.287, p < 0.05), while brand image had no significant effect (β = 0.231, p > 0.05). Both antecedent variables were shown to have a significant effect on customer loyalty, with perceived value showing a stronger influence (β = 0.456) than brand image (β = 0.318). Customer loyalty partially mediated the relationship between perceived value and customer citizenship behavior (β = 0.177, p < 0.05), but did not mediate the relationship between brand image and customer citizenship behavior. The research model was able to explain 65.1% of the variability in customer citizenship behavior. The study concluded that companies need to prioritize increasing perceived value through strategies that focus on superior product quality and excellent customer service to encourage customer citizenship behavior, as well as developing comprehensive loyalty programs to strengthen long-term relationships with consumers.